Inside Ownership, Financial Performance and Firm Size as Moderating Variables - HERMUNINGSIH, SRI; KUSUMA, HADRI; IQBAL FASA, MUHAMMAD; PANJAITAN, ROYMON (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT This study aimed at investigating the connection concerning inside ownership and the financial implementation of firms registered on the Indonesia Ordinary Interchange. Samples were collected from 14 businesses from food an beverages buyer sub-sector in the period of 2014-2018 by means of purposive testing technique. The data were studied by Multiple Linear Regression and Moderated Regression Analysis. The outcome showed that a stable number of stocks could determine the decision for investment opportunities. Besides, firm size contributed to reinforce the association concerning privileged property and profit-oriented companies in term of financial performance. RESUMEN Este estudio tuvo como objetivo investigar la conexión entre la propiedad de información privilegiada y la implementación financiera de las empresas registradas en el intercambio ordinario de Indonesia. Se recolectaron muestras de 14 negocios desde el subsector de compra de comidas y bebidas en el período 2014-2018 mediante la técnica de prueba intencional. Los datos se estudiaron agotando el análisis de regresión lineal múltiple y regresión moderada. El resultado mostró que un número estable de acciones podría determinar la decisión de oportunidades de inversión. Además, el tamaño de la empresa contribuyó a reforzar la asociación con respecto a la propiedad privilegiada y las empresas con ánimo de lucro en términos de rendimiento financiero.